Critical language teacher education: A duoethnography of teacher educators' identities and agency. (June 2021) - Banegas, Darío Luis; Gerlach, David
Abstract: The aim of this paper is to describe the identity and agency of two teacher educators who explored critical language teacher education by following a comprehensive sexuality education (CSE) approach and a gender perspective in their English language teaching methodology modules. The study adopted a duoethnographic approach through which the two teacher educators (based in Argentina and Germany respectively) reflected on their practice by maintaining regular Zoom meetings and a shared online document for written dialogue. In the duoethnography, the teacher educators concentrated on describing and reflecting on their motivations to embrace CSE through a critical view of education and how these motivations impacted on the design and delivery of their modules. In addition, they reflected on their identity and agency to identify what aspects of their professional selves acted as conducive factors. Findings show that the teacher educators' sense of social justice and responsibility exerted a pivotal role on their agency and identity as critical language teacher educators. Highlights: Duoethnography is used to reflect on teacher educator identity and agency. Critical language teacher education can support a gender perspective approach. Identity and agency are context-bound and expressions of social responsibility.